The impact of monetary policy variables on Iraq’s recessionary inflation for the period 2004-2021 - Mustafa, Farhad; Naima, Samir; Obaid, Salah (Humanities Journal of University of Zakho, 2024)
The present study aimed at finding out the effect of monetary policy on stagflation via analysing the data on the Iraqi economy from 2004 to 2021. The study adopted the analytical inductive approach in presenting the concept of monetary policy and its variables impact in addressing the problem of stagflation in Iraq, through the use of the quantitative and analytical method to measure that relationship. The study found that these tools have an effect on stagflation. The results also showed that 81% of the changes that occur in stagflation are caused by monetary policy variables. and the significant impact on these variables was the exchange rate, and this is in agreement with the essence of the theory according to the characteristics of the Iraqi economy.